2015
DOI: 10.1080/00224545.2015.1129302
|View full text |Cite
|
Sign up to set email alerts
|

Sense of community coherence and inter-religious relations

Abstract: The current article attempts to broaden the individual-based concept of sense of coherence to the community level. We examine sense of community coherence and its connection with perceptions of collective narratives and acculturation tendencies in the social context of Palestinian Muslims and Christians living in Israel. Questionnaires that were developed and adapted for the unique population in this study were distributed to a representative sample of 1034 Muslims (455 males) and 720 Christians (354 males), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…These finding echoed what Mana et al. () found in their study on Muslim and Christian minorities in Israel. Reasonably, prolonged separation could also increase EPSOC, and we cannot exclude that a circular relationship connects these two variables.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These finding echoed what Mana et al. () found in their study on Muslim and Christian minorities in Israel. Reasonably, prolonged separation could also increase EPSOC, and we cannot exclude that a circular relationship connects these two variables.…”
Section: Discussionsupporting
confidence: 89%
“…As for the role played by immigrants’ PSOC in acculturation behaviors, quantitative studies that have explicitly addressed this relationship and proposed hypotheses are virtually nonexistent. To the best of our knowledge, there is only a recent study conducted among minority religious groups in Israel (Mana, Sagy, & Srour, ), which revealed that sense of coherence—which, like PSOC, involves the perception that the community can support its members and meet their needs, and that it is meaningful to them—was positively related to the tendency for separation and negatively related to the tendency for integration and assimilation.…”
Section: Psoc and Mpsoc Within Immigrant Groupsmentioning
confidence: 99%
“…The relations between the conflicted groups were examined by the levels of adherence to in-group as well as acceptance of the out-group collective narratives and acculturation attitudes. One of the studies was conducted among Palestinian Muslims and Christians in Israel (Mana et al, 2015). The results revealed that strong community sense of coherence (CSOC) was correlated with higher levels of acceptance of the in-group collective narrative and with lower levels of acceptance of the out-group collective narratives.…”
Section: Introductionmentioning
confidence: 99%
“…Just recently, however, a few studies have attempted to connect salutogenesis and SOC to other social concepts such as intergroup relations, openness toward the "other" and readiness to reconcile (Mana, Sagy, & Srour, 2015;. These studies connect the salutogenic paradigm with other interdisciplinary models and concepts such as social identity (Tajfel, 1981), acculturation (Berry, 1990), conflict studies (Bar-Tal, 1998), or peace and reconciliation (Nadler, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Just recently, however, a few studies have attempted to connect salutogenesis and SOC to other social concepts such as intergroup relations, openness toward the "other" and readiness to reconcile (Mana, Sagy, & Srour, 2015;Sagy, 2014;Srour, 2015). These studies connect the salutogenic paradigm with other interdisciplinary models and concepts such as social identity (Tajfel, 1981), acculturation (Berry, 1990), conflict studies (Bar-Tal, 1998), or peace and reconciliation (Nadler, 2012).…”
Section: Introductionmentioning
confidence: 99%